Beneficial Effect of N-Carbamylglutamate in a Neonatal Form of Multiple Acyl-CoA Dehydrogenase Deficiency - Sinziana Stanescu; Amaya Belanger-Quintana; Carlos Alcalde Martin; Celia Pérez-Cerdá Silvestre; Begoña Merinero Cortés; Belen Gonzalez Pérez; Carmen Fernández García-Abril; Francisco Arrieta Blanco; Esperanza Palacios Valverde; Mercedes Martínez-Pardo Casanova (Hindawi Limited, 2020)
Background. Multiple acyl-CoA dehydrogenase deficiency is an autosomal recessive disorder of the amino acid metabolism and fatty acid oxidation due to the deficiency of the electron transfer protein or electron transfer protein ubiquinone oxidoreductase. The clinical picture ranges from a severe neonatal lethal presentation to late myopathic forms responsive to riboflavin. Up to now, there is no effective treatment for the neonatal form, which exhibits severe metabolic acidosis, hyperammonemia, hypoketotic hypoglycemia, and rhabdomyolysis. We present the case of a child who has had a good long-term outcome after a typical neonatal onset, with a dramatic drop in ammonia levels during the initial metabolic decompensation crisis and adequate control even during intercurrent diseases thereafter with N-carbamylglutamate treatment.